The economic impact of Research and Extension on the improved - souleymane, ouedraogo kembo (Advances in Social Sciences Research Journal, 2018)
This study aims to assess the economic impact of research and extension as for improved cowpea varieties in Burkina Faso. Indeed, the effectiveness of the use of financial resources allocated to research and extension is a concern for donors and governments of different countries. The economic surplus model was used as an analytical tool for this study. Thus, data were collected from research, extension and statistical data production structures. This method evaluates the impacts in terms of shift of the supply curves. The results of the model show that it is benefitting to invest in cowpea research. In fact, in this study, the internal return rate is about 48% for the period ranging from 2000 to 2013, with a net added value of more than 121 billion FCFA. Such high rates could only be achieved through the relevance of the research results and their dissemination / adoption. Therefore, for a development of the cowpea sector and an improvement of producers ‘income, the investment in the research is essential.